2014
DOI: 10.5897/ajar09.758
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficiency of microspore culture of Brassica campestris ssp. pekinensis (Chinese cabbage)

Abstract: We selected two cultivars of Brassica campestris ssp. pekinensis (Chinese cabbage), 'Futian 50' and 'Changkuai,' to investigate the factors that influence microspore embryogenesis and plantlet regeneration. We have also discussed some protocols for the induction culture of microspore-derived embryos and for rooting and transplantation of microspore-derived plantlets. We obtained the following findings in our study. Although NAA promotes the development of embryo and reduces the percentage of abnormal embryos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…Many researchers have also used culture media without plant growth regulators. However, Han, Ye, and Feng (2014) reported that BAP stimulates embryogenesis in B. campestris at a concentration of 0.4 mg/L. The results of our study did not fully correspond with the abovementioned works.…”
Section: Discussioncontrasting
confidence: 98%
“…Many researchers have also used culture media without plant growth regulators. However, Han, Ye, and Feng (2014) reported that BAP stimulates embryogenesis in B. campestris at a concentration of 0.4 mg/L. The results of our study did not fully correspond with the abovementioned works.…”
Section: Discussioncontrasting
confidence: 98%
“…A very similar response has been observed in Chinese cabbage (Brassica campestris spp. pekinensis) (Han et al, 2014), where the addition of AC increased plantlet regeneration. In several subspecies of Brassica rapa, further development of obtained microsporederived embryos can be approached in different ways (Takahashi, 2012).…”
Section: Discussionmentioning
confidence: 99%